Effects of 445‐nm Laser on Vessels of Chick Chorioallantoic Membrane with Implications to Microlaryngeal Laser Surgery. (18th January 2021) - Nguyen, Duy Duong; Pang, Jing‐Yin; Madill, Catherine; Novakovic, Daniel
Abstract : Objective: Previous research has shown that effective application of angiolytic lasers in microlaryngeal surgery is determined by wavelength, pulse width (PW), and fluence. Recently, a 445‐nm (blue) laser (BL) has been developed with a potentially greater hemoglobin absorption than previous lasers. The chick chorioallantoic membrane (CAM) represents a suitable model for testing various settings to find out the most optimal settings of this laser. This study used the CAM model to examine whether successful photoangiolytic effects could be obtained using BL. Methods: Seven hundred and ninety three third‐order vascular segments of viable CAM were irradiated using BL via 400‐μm diameter fiber, 1 pulse/second, with PW and power varied systematically at standardized fiber‐to‐vessel distances of 1 and 3 mm. Outcome measures including vessel ablation rate (AR), rupture rate (RR), and visible tissue effects were analyzed using Chi‐square test. Results: Energy levels of 400, 540, and 600 mJ (per pulse) were most effective for vessel ablation. A working distance of 3 mm resulted in higher ablation and less vessel rupture compared with 1 mm at these optimal energy levels. At 3 mm, a longer PW resulted in higher AR. At 1 mm, AR increased with shorter PW and higher power. The 1‐mm working distance resulted in lower tissue effects than 3 mm. Conclusion: Findings in this study showed that BL was effective in vessel ablation using relevant combination of working distance, PW, and energy levels. To obtain high AR, longer working distance plus longer PW was required and if working distance was reduced, shorter PW should be set. Level of Evidence: NA Laryngoscope, 131:E1950–E1956, 2021